Systematics of Quaternary Squamata from Cuba - Pedroso, Ernesto Aranda (2019)
The paleontology of reptiles in the Caribbean is a topic of great interest to understand how the current fauna of the area was constituted from colonization and extinction of their groups. The largest number of fossils belongs to Squamata, ranging from the Eocene to our days. The registry covers all the islands of the Greater Antilles, most of the Lesser Antilles, and of the Bahamas. Cuba, the largest island of the Antilles, has a relatively sparse Squamata fossil record, with 11 known species from 10 locations, distributed in the West and Center of the Country. However, there are many other fossils deposited in biological collections without identification that could better clarify the history of their reptile fauna. A total of 328 fossils from three paleontological collections were selected for their analysis, searching osteological characteristics that would serve to diagnose them at the lowest possible taxonomic level, and compare them with other fossils and recent species. In the present work, the Squamata fossil record is increased, both in the number of species and in the number of localities. The registry is extended to practically all of the Cuban territory. Fossil remains belonging to previously reported species are confirmed, such as Leiocephalus cubensis, L. carinatus, Tarentola americana, Chilabothrus angulifer, and Cubophis cantherigerus. Fossils of Amphisbaena, Pholidoscelis auberi, and Leiocephalus macropus are described for the first time. Besides, other fossils belonging to the genera Tarentola, Leiocephalus, and Chilabothrus but different from the species that currently inhabit the archipelago, are described. These results show that the Squamata fossil record in Cuba is broader than what was previously considered, despite being composed of very fragile and small fossils with little potential for fossilization. For the paleontology of Squamata the description of new taxa and record of new localities in Cuba, are the first steps for more integrating studies on biological diversity, evolution, biogeography, paleoenvironment among others that contribute to the understanding of the fauna in the Caribbean region.